Impact of multimorbidity on the first ts/bDMARD effectiveness and retention rate after two years of follow-up in patients with rheumatoid arthritis from the BIOBADASER registry - Calvo-Gutiérrez, Jerusalem; López-Medina, Clementina; Otero-Varela, Lucía; Escudero-Contreras, Alejandro; Ortega-Castro, Rafaela; Ladehesa-Pineda, Lourdes; Campos, Cristina; Bernabeu-Gonzalvez, Pilar; Pérez-Gómez, Ana; García-Dorta, Alicia; Ruiz-Montesino, Dolores; Pombo-Suarez, Manuel; et al. (Arthritis research & therapy, 2024)
Background Patients with Rheumatoid Arthritis (RA) have a higher prevalence of comorbidities compared to the general population. However, the implications of multimorbidity on therapeutic response and treatment retention remain unexplored. Objectives: (a) To evaluate the impact of multimorbidity on the effectiveness of the first targeted synthetic or biologic disease-modifying antirheumatic drug (ts/bDMARD), in patients with RA after 2-year follow-up; (b) to investigate the influence of multimorbidity on treatment retention rate. Methods Patients with RA from the BIOBADASER registry exposed to a first ts/bDMARDs were included. Patients were categorized based on multimorbidity status at baseline, defined as a Charlson Comorbidity index (CCI) score ≥ 3. A linear regression model, adjusted for sex and age, was employed to compare the absolute DAS28 score over time after ts/bDMARD initiation between the two groups. The Log-Rank test and Kaplan-Meier curve were used to compare the retention rates of the first ts/bDMARD between the groups. Results A total of 1128 patients initiating ts/bDMARD were included, with 107 (9.3%) exhibiting multimorbidity. The linear regression model showed significantly higher DAS28 (beta coefficient 0.33, 95%CI:0.07–0.58) over a two-year period in patients with multimorbidity, even after adjusting for age and sex. Finally, no differences in the ts/bDMARD retention rate were found between groups (median 6.94–6.96 years in CCI < 3 vs. 5.68–5.62 in CCI ≥ 3; p = 0.610). Conclusions Multimorbidity in patients with RA was associated with greater DAS28 scores within the first two years after ts/bDMARD initiation, in comparison with patients without multimorbidity. A slightly shorter retention rate was found in patients with multimorbidity, although the difference was non-significant.